2023
DOI: 10.3390/ijms24119456
|View full text |Cite
|
Sign up to set email alerts
|

Relative Humidity and Its Impact on the Immune System and Infections

Abstract: Relative humidity (RH) represents an underestimated outdoor and indoor environmental parameter. Conditions below and above the optimal range could facilitate infectious transmission as well as the exacerbation of respiratory diseases. The aim of this review is to outline the consequences for health of suboptimal RH in the environment and how to limit this negative impact. RH primarily affects the rheological properties of the mucus, modifying its osmolarity and thus the mucociliary clearance. The integrity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Exposure to cold caused pediatric pneumonia hospital admissions to increase by approximately 5.1% compared with non-cold exposure (p < 0.05) (40). Dry air during cold events can lead to the drying and irritation of mucous membranes in the respiratory tract, impairing their protective function and facilitating the entry of viruses and bacteria into the airways (41). We observed that extreme cold is an important risk factor for pediatric pneumonia outpatient visits.…”
Section: Discussionmentioning
confidence: 75%
“…Exposure to cold caused pediatric pneumonia hospital admissions to increase by approximately 5.1% compared with non-cold exposure (p < 0.05) (40). Dry air during cold events can lead to the drying and irritation of mucous membranes in the respiratory tract, impairing their protective function and facilitating the entry of viruses and bacteria into the airways (41). We observed that extreme cold is an important risk factor for pediatric pneumonia outpatient visits.…”
Section: Discussionmentioning
confidence: 75%
“…Relative humidity is, at all temperatures and pressures, defined as the ratio of the water vapor pressure to the saturation water vapor pressure (over water) at the gas tem-perature [62]. The definition of relative humidity makes this environmental parameter difficult to measure and control because it is a ratio rather than an absolute value.…”
Section: Discussionmentioning
confidence: 99%
“…Humidity and carbon dioxide (CO 2 ) play pivotal roles in the design of infection control methods within indoor environments [ 39 ]. Maintaining an optimal relative humidity (RH) is crucial, as studies have shown a significant correlation between humidity levels and infection rates [ [40] , [41] , [42] ]. The role of humidity in reducing infection rates involves a complex interplay of biological and physical factors.…”
Section: Introductionmentioning
confidence: 99%